Parenting Patterns and the Development of Children's Noble Character: A Qualitative Study in Mibo Village, Banda Aceh - Sulaiman, Muhammad Bakil; Zain, Arifin; Duri, Rofiqa (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2025)
This study aims to explore the role of parents in cultivating noble character in children in Mibo Village, Banda Aceh. It is driven by the lack of contextual research on parenting strategies in Acehnese communities, which integrate religious values, local customs, and the influence of modernization. Employing a descriptive qualitative approach, the study involved five parents selected through purposive sampling. Data were collected using semi-structured interviews, non-participant observation, and documentation, and were analyzed through the interactive model of Miles and Huberman. Findings revealed that democratic parenting was predominantly applied, supported by strategies such as role modeling, discussion, storytelling, and social engagement. The main challenges included peer influence, digital technology exposure, and inconsistent rule enforcement by parents. This study contributes by highlighting the critical synergy between family and social environments in moral education and recommends the development of culturally rooted family mentoring programs.